Synergistic effects of web reinforcement and hybrid fibres on shear performance of continuous deep beams with unsymmetrical web openings - Fan, Shengxin (2024)
Application of fibre-reinforced concrete or novel web reinforcement detailing could be an effective way to enhance structural behaviour of continuous deep beams with web openings. However, there are very few experimental works studying the synergistic effects of these two methods. Therefore, an experimental programme is introduced in this paper to study synergistic effects of shear reinforcement and hybrid fibres on shear strength of nine double-span deep beams with unsymmetrical web openings (denoted as pierced span). The test specimens were designed to consist of a pierced beam span with a web opening and an adjacent solid beam span. The spans with openings were designed with different shear reinforcement configurations. It was experimentally shown that provision of sufficient web steels above and below web openings has the most important and beneficial effect on ultimate shear strength of the pierced spans. Besides, a tailored steel reinforcing method was also proposed that is capable of improving strut capacity near the web opening. In addition, adoption of hybrid fibre reinforcement led to enhanced crack-opening resistance, ultimate shear strength and shear deformation. Based on the research outcomes, it was recommended to adopt the proposed detailing method or fibre reinforcement dosage for shear strength enhancement of continuous deep beams with web openings. Furthermore, an analytical model was adopted to the shear strength of continuous deep beams accounting for web openings, steel stirrups, and hybrid fibres, which yielded safe predictions.